(untitled) (Revista de História da UEG (REVHIST), 2021)
The transformations of the European historiography since the second half of the XVIII century impelled to a meaningful change in the ways the past was related. Far beyond the sacred historiography and the classic narrative, the object of the historiography also changed, introducing new concepts and subjects. The aim of this article is to study the manifold paths available to the enlightened historiography in Spain, reasserting the country as one of the settings of the intellectual revolution of the age. For this purpose, it will be reviewed in particular the concept of Empire, because it carried many temporal extracts and it was being challenged in a world where nations loomed, so as the new commercial and polished society. Therefore, the article contributes to the history of Concepts in the Modern Age. Keywords: America. Spain. Rome. Bourbon Reforms. Imperialism.